La otredad del yo en miradas y cuerpos ajenos: Kentukis de Samantha Schweblin - Bakucz, Dóra (Verbum – Analecta Neolatina, 2021)
The aim of this article is to study how communication and human relationships can be affected by possibilities offered by technology in Samantha Schweblin’s novel, Kentukis. The article proposes to analyze the narrative from three different perspectives: the borders or limits that fade in the virtual space, the inequalities that involve the relationships of the characters in the online world, and of the identities affected by the development (or regression) of these relationships. The conclusion is that the studied aspect of the novel is interpretable outside the category of science fiction and able to analyze – using results of other disciplines like sociology – as a metaphor of conditions generated by the social media of our times.